Earlier age of sex and substance use initiation is associated with unique hormone profiles during social evaluative threat in Mexican American adolescents. (November 2020) - Johnson, Megan; Shirtcliff, Elizabeth A.; van Dammen, Lotte; Dahl, Ronald E.; Gonzales, Nancy; Harley, Kim G.; Rauch, Stephen; Greenspan, Louise C.; Eskenazi, Brenda; Deardorff, Julianna
Highlights: Less developed Mexican-origin pubertal boys at age 14 reported earlier risk taking. Mexican-origin boys in pubertal transition had high cortisol reactivity to social threat. High cortisol reactivity predicted early alcohol use initiation in Mexican-origin girls. High testosterone reactivity predicted early oral sex for Mexican-origin girls. More pubertally advanced adolescents are at increased risk for earlier risk taking. Abstract: Latinx adolescents are at a disproportional risk for poor sexual and reproductive health outcomes (STIs, adolescent pregnancy) compared to other ethnic groups. They also report high rates of alcohol and drug use that are similar to non-Hispanic White youth. The hormonal underpinnings of the emergence of sex and substance use behaviors among Latinx adolescents remain understudied however. Pubertal shifts in motivation and reward-seeking in social situations are closely tied to the emergence of risky sexual and substance use behaviors. The experience of developing earlier or later than same age peers may increase stress (cortisol) reactivity during social evaluative situations leading to more risky behavior. Further, testosterone can be responsive to social evaluative threat (SET) and is linked to status-seeking behavior, including risk-taking. The current study sought to unravel the complex relationship between cortisol and testosterone responsivity to social evaluative threat, pubertal status, and the emergence of sex and drug use among US-born Mexican-origin youth growing up in an agricultural community. Mexican American 14-year olds (N = 234, 54% female) from the Center for Health Assessment of Mothers and Children (CHAMACOS) participated in the Trier Social Stress Test. Cortisol and testosterone were assayed from saliva. At 16, youth reported on age at vaginal and oral sex initiation, and alcohol and marijuana use initiation. Hierarchical regressions examined cortisol and testosterone reactivity, and pubertal status within each sex to predict the onset of these risky behaviors. Results indicated that boys who were less developed than their same-aged peers or with lower testosterone reactivity and elevated cortisol reactivity to the TSST reported the earliest sex and substance use initiation. For girls, higher cortisol reactivity predicted earlier alcohol use initiation, and higher testosterone reactivity predicted earlier oral sex. Our results suggests it is important for health care providers to not overlook Latinx boys who may look younger in discussions about mitigating risk. Latinx girls under increased stress may be more likely to try to self-medicate with alcohol, and potentially other drugs.